Modelling yield response of a traditional and a modern barley cultivar to different water and nitrogen levels in two contrasting soil types - Abeledo, Leonor Gabriela (2011)
The importance of yield improvement at farm conditions is highly dependent on the interaction between genotype and environment. The aim of the present work was to assess the attainable yield of a traditional and a modern malting barley cultivar growing under a wide range of soil nitrogen (N) availabilities and different water scenarios (low, intermediate and high rainfall conditions during the fallow period and throughout the crop cycle) considering a 25-year climate dataset for two sites (a shallow and a deep soil) in the Pampas, Argentina. For that purpose, a barley model was first calibrated and validated and then used to expand field research information to a range of conditions that are not only much wider but also more realistic than experiments on experimental farms. Yield of the modern cultivar was at least equal to (under the lowest yielding conditions) or significantly higher (under most growing conditions) than that of the traditional cultivar. Averaged across all the scenarios, yield was ~20% higher in the modern than in the traditional cultivar. The average attainable yield represented 42% of the yield potential in the shallow and 79% in the deep soil profiles. Yield advantage of the high yielding cultivar was based on using N more efficiently, which not only determined higher attainable yields but also reduced the requirements of soil N to achieve a particular yield level. Farmers would face little risk in adopting higher yielding cultivars in both high and low yielding environments and even in the latter ones N fertilisation could be beneficial in most years.